Melatonin enhances cell death and suppresses the metastatic capacity of ovarian cancer cells by attenuating the signaling of multiple kinases - Cucielo, Maira Smaniotto [UNESP]; Freire, Paula Paccielli; Emílio-Silva, Maycon Tavares [UNESP]; Romagnoli, Graziela Gorete; Carvalho, Robson Francisco [UNESP]; Kaneno, Ramon [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Delella, Flávia Karina [UNESP]; Reiter, Russel J.; Chuffa, Luiz Gustavo de Almeida [UNESP] (My University, 2023)
Background: Ovarian cancer is a highly aggressive disease that is frequently diagnosed in advanced stages. Melatonin, with its numerous antitumor properties, holds great promise in cancer treatment. Herein, we investigated the effects of melatonin on apoptosis, cell migration, and kinase levels in human ovarian carcinoma SKOV-3 cells and determined whether these effects are mediated by the activation of the MT1 receptor. Methods: SKOV-3 cells were exposed to different concentrations of melatonin based on the presence of MT1 receptor, and we also performed specific silencing of the melatonin receptor gene MTNR1A. Results: Our findings revealed that melatonin reduced cell viability as shown by the MTT assay, and flow cytometry analysis showed increased rates of apoptosis and necrosis in all melatonin-treated cells. Melatonin significantly decreased the migratory and invasive capacities of the cells. Propidium iodide labeling indicated that melatonin induced cell cycle arrest by reducing DNA content in the S and G2/M phases in SKOV-3 cells. Additionally, the levels of AKT, ERK1/2, JNK, CREB, p70S6K, STAT3/5, and p38 MAP kinase involved in cell survival, proliferation, motility, and stress responses were depressed by melatonin and further reduced after MT1 knockdown. These molecules were found to be associated with lower overall survival in ovarian cancer patients. Conclusions: Melatonin had obvious oncostatic actions on ovarian cancer cells, and MT1 receptor knockdown intensified its antitumor effect. The inhibition of the MT1 receptor resulted in a substantial reduction in the migratory and invasive capacities of the cells, suggesting its potential as a therapeutic target for the treatment of ovarian cancer.
Keywords: Apoptosis; Kinase signaling; Melatonin; Migration; MT1 receptor; SKOV-3 cells